Do Your Own Research (DYOR) And Not Financial Advice (NFA) As A Liability-Limiting Doctrine In Indonesian Capital Market Law - Rifqon Khairazi; I Putu Endra Wijaya Negara; Berd Elkiopas Pelupessy (Indonesian Journal of Innovation Multidisipliner Research, 2026)
The rapid digitalization of capital markets has transformed the production and dissemination of investment information, enabling individual investors to share analyses and opinions through social media and online platforms. This development has increased the use of disclaimers such as Do Your Own Research (DYOR) and Not Financial Advice (NFA), which are frequently employed to indicate that published content does not constitute professional investment advice. Despite their widespread adoption, the legal status and liability-limiting function of these disclaimers remain largely unexplored within Indonesian capital market law. This study examines whether DYOR and NFA may operate as normative instruments that limit legal responsibility arising from publicly disseminated investment analyses. Employing a normative juridical method with statutory, conceptual, and comparative approaches, the research analyzes Indonesian capital market regulations alongside relevant doctrines of liability, reliance, and financial communication. The study finds that DYOR and NFA should not be understood merely as informal expressions but as contextual disclaimers that may clarify the absence of advisory relationships and reduce reasonable reliance by audiences. However, their effectiveness depends on the substance of the communication rather than the disclaimer itself. Where content contains personalized recommendations, inducement of reliance, misleading statements, or undisclosed conflicts of interest, disclaimers cannot negate regulatory obligations or legal liability. The study proposes doctrinal criteria for distinguishing protected investment opinions from actionable investment advice and argues that Indonesian regulators should adopt a substance-based approach that balances investor protection with freedom of expression in digital investment discourse.